2017
DOI: 10.1016/j.sigpro.2016.06.030
|View full text |Cite
|
Sign up to set email alerts
|

A signal processing methodology for assessing the performance of ASTM standard test methods for GPR systems

Abstract: Ground penetrating radar (GPR) is one of the most promising and effective non-destructive testing techniques (NDTs), particularly for the interpretation of the soil properties. Within the framework of international Agencies dealing with the standardization of NDTs, the American Society for Testing and Materials (ASTM) has published several standard test methods related to GPR, none of which is focused on a detailed analysis of the system performance, particularly in terms of precision and bias of the testing v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…where A0 [V] is the maximum absolute value of the signal amplitude reflected at the interface of the air/ballast surface; APEC [V] is the maximum absolute value of the amplitude reflected by a metal sheet placed at the bottom of the ballast system and larger than the antenna footprint (e.g. [36,37]). This is defined as the effective area illuminated by the antenna on the investigated surface [38].…”
Section: The Surface Reflection Methodsmentioning
confidence: 99%
“…where A0 [V] is the maximum absolute value of the signal amplitude reflected at the interface of the air/ballast surface; APEC [V] is the maximum absolute value of the amplitude reflected by a metal sheet placed at the bottom of the ballast system and larger than the antenna footprint (e.g. [36,37]). This is defined as the effective area illuminated by the antenna on the investigated surface [38].…”
Section: The Surface Reflection Methodsmentioning
confidence: 99%
“…These two equations imply the presence of the two statistical moments (i.e. mean and variance) of the testing variable, that strictly depend on the characteristics of the signal under investigation (see [48] and references therein for further details). In all the analysed cases, the 1000 MHz GPR system is characterized by the worst performance, again due to the lower resolution power of the selected antenna frequency (i.e.…”
Section: Experimental Outcomesmentioning
confidence: 99%
“…Experimental setup for the laboratory measurements.The ground-coupled multi-frequency GPR system RIS 99-MF, equipped with 600 MHz and 1600MHz monostatic antenna frequencies, was set to collect 512 sample size data with a time window of 40 ns (time step of acquisition equal to 7.83 × 10 -2 ns). In addition, three air-coupled GPR systems, equipped with 1000 MHz (RIS Hi-Pave HR1 1000), and 2000 MHz (RIS Hi-Pave HR1 2000 and RIS Hi-Pave HR1 2000 NA) antenna frequencies, were used to collect data at 40 cm height from the surface of the ballast[48]. Concerning the 2000 MHz antenna systems, one version for the European (EU) market (from now on, referred to as "2 GHz EU") and one low-powered antenna version for the North American (NA) market (from now on, referred to as "2 GHz NA") were used.…”
mentioning
confidence: 99%
“…At the same time, the dimensions of the real domain must comply with the minimum requirements in terms of (i) real‐life design thickness for a ballast layer (Roberts et al., ) and (ii) use of testing equipment for a comprehensive investigation of the ballast material (i.e., avoiding any edge affect). In regard to this latter parameter, the boundaries for avoiding edge effects with the GPR system used in this study are found according to the procedures discussed in ASTM D6087‐08 () and Benedetto and Tosti ().…”
Section: Methodsmentioning
confidence: 99%